Seasonal habitat and diet partitioning between two sympatric bovid species in Pendjari Biosphere Reserve (northern Benin): waterbuck and western kob. - DJAGOUN, CHABI A.M.S.; KASSA, B; MENSAH, GUY APOLLINAIRE; SINSIN, Brice A. (My University, 2013)
Niche theory suggests differential use of shared resources facilitates coexistence of species in a community. In this study we used the faecal stable isotope analysis with observations along transect lines perpendicular to the Pendjari River. This was to examine seasonal habitat features and diet partitioning between two sympatric bovid species waterbuck (Kobus ellipsiprymnus) and western kob (Kobus kob) in the Pendjari Biosphere Reserve. In support of niche partition hypothesis, diets of western kob and waterbuck diverged significantly along both faecal selection axes (d 13 C and d N) during the resource-limited period of the dry season as opposed to wet season when there is resource abundance. Western kob and waterbuck resource partitioning does not occur only on the basis of diet segregation but also some habitat variables play an important role in the coexisting system. Findings support the niche partition hypothesis, where morphologically, ecologically and closely related sympatric species segregate at least in one of the niche dimensions to allow coexistence. The two bovid species were observed to diverge largely along distance to water source gradient. The results provided empirical evidence that habitat features acts as an additional dimension over which herbivores partition resources.
Keywords: niche overlap; habitat selection; coexistence.